REVISITING RELEVANT APPROACHES FOR THE STUDY OF LANGUAGE AND INTERCULTURAL COMMUNICATION - Yunxia, Zhu (International Journal of English Studies, 2008)
This paper revisits relevant approaches used for the study of language and intercultural communication, in particular, in the area of comparing English and Chinese discourse structures. Kaplan's (1966) work has a great impact on the various approaches in this area such as Kirkpatrick (1991; 1993) and Zhu (1997). This paper specifically investigates the approaches focusing on Kaplan's proposal on the circularity and linearity of rhetorical structures. It has been found that these approaches were largely based on rhetorical rules such as pianzheng fuju or the subordinate-main structure ( Kirkpatrick 1991; 1993). This paper then argues that the intercultural and language study should incorporate cross-cultural pragmatics and genre study in order to offer more holistic principles relating to cultural values, politeness, and communicative intent.